Benefits of not smoking during pregnancy for non-Aboriginal women and their babies in New South Wales, Australia: a record linkage study
Background Smoking rates among pregnant women in New South Wales (NSW) have plateaued at 8-9%. To inform relevant smoking reduction efforts, we aimed to quantify the benefits of not smoking during pregnancy for non-Aboriginal NSW mothers and their babies. The benefits of not smoking during pregnancy for NSW Aboriginal mothers have previously been described. These data are important inputs in modelling health and economic impacts of smoking cessation interventions. Methods This population-based cohort study used linked-data from routinely collected data sets. Not smoking during pregnancy was the exposure of interest among all NSW non-Aboriginal women who became mothers of singleton babies in 2012-2016. Unadjusted and adjusted relative risks (aRR) were used to examine associations between not smoking during pregnancy and adverse outcomes including severe morbidity, inter-hospital transfer, perinatal death, preterm birth and small-for-gestational age. Population attributable fractions (PAFs) were calculated to quantify adverse perinatal outcomes avoided in the population if all mothers were non-smokers. Results Compared with babies born to mothers who smoked during pregnancy, babies born to non-smoking mothers had a lower risk of all adverse perinatal outcomes including perinatal death (aRR